SAKK 16/14: Durvalumab in Addition to Neoadjuvant Chemotherapy in Patients With Stage IIIA(N2) Non–Small-Cell Lung Cancer—A Multicenter Single-Arm Phase II Trial. Issue 26 (10th September 2021) - Rothschild, Sacha I.; Zippelius, Alfred; Eboulet, Eric I.; Savic Prince, Spasenija; Betticher, Daniel; Bettini, Adrienne; Früh, Martin; Joerger, Markus; Lardinois, Didier; Gelpke, Hans; Mauti, Laetitia A.; Britschgi, Christian; et al.
Abstract : PURPOSE: For patients with resectable stage IIIA(N2) non–small-cell lung cancer, neoadjuvant chemotherapy with cisplatin and docetaxel followed by surgery resulted in a 1-year event-free survival (EFS) rate of 48% in the SAKK 16/00 trial and is an accepted standard of care. We investigated the additional benefit of perioperative treatment with durvalumab. METHODS: Neoadjuvant treatment consisted of three cycles of cisplatin 100 mg/m 2 and docetaxel 85 mg/m 2 once every 3 weeks followed by two doses of durvalumab 750 mg once every 2 weeks. Durvalumab was continued for 1 year after surgery. The primary end point was 1-year EFS. The hypothesis for statistical considerations was an improvement of 1-year EFS from 48% to 65%. RESULTS: Sixty-eight patients were enrolled, 67 were included in the full analysis set. Radiographic response rate was 43% (95% CI, 31 to 56) after neoadjuvant chemotherapy and 58% (95% CI, 45 to 71) after sequential neoadjuvant immunotherapy. Fifty-five patients were resected, of which 34 (62%) achieved a major pathologic response (MPR; ≤ 10% viable tumor cells) and 10 (18%) among them a complete pathologic response. Postoperative nodal downstaging (ypN0-1) was observed in 37 patients (67%). Fifty-one (93%) resected patients had an R0 resection. There was no significant effect of pretreatment PD-L1 expression on MPR or nodal downstaging. The 1-year EFS rate was 73% (two-sided 90% CI, 63 to 82). Median EFS and overall survival were not reached after 28.6 months of median follow-up. Fifty-nine (88%) patients had an adverse event grade ≥ 3 including two fatal adverse events that were judged not to be treatment-related. CONCLUSION: The addition of perioperative durvalumab to neoadjuvant chemotherapy in patients with stage IIIA(N2) non–small-cell lung cancer is safe and exceeds historical data of chemotherapy alone with a high MPR and an encouraging 1-year EFS rate of 73%.